Toxic effects of male Perna viridis gonad exposed to BaP, DDT and their mixture: A metabolomic and proteomic study of the underlying mechanism. Issue 1 (5th January 2016) - Song, Qinqin; Zheng, Pengfei; Qiu, Liguo; Jiang, Xiu; Zhao, Hongwei; Zhou, Hailong; Han, Qian; Diao, Xiaoping
Highlights: BaP did not show obvious metabolite changes in gonad of male green mussels. Metabolite changes of DDT show disturbance of osmotic regulation and energy level. Metabolomics results show that male gonad was more sensitive to DDT than BaP. Proteomic responses revealed the different regulation pathway between BaP and DDT. Proteomics and metabolomics provided an insightful view into the effects of EEs. Abstract: Benzo(a)pyrene and dichlorodiphenyltrichloroethane are typical persistent organic pollutants, and also the widespread environmental estrogens with known toxicity towards green mussels Perna viridis . In this study, the toxicological effects of BaP and DDT and their mixture were assessed in green mussel gonads using proteomic and metabolomic approaches. Metabolomics by NMR spectroscopy revealed that BaP did not show obvious metabolite changes in the gonad of male green mussel. DDT mainly caused some disturbance of osmotic regulation and energy metabolism by changing BCAAs, alanine, threonine, arginine, etc., unknown metabolite (3.53 ppm), glycine, homarine and ATP at different levels. However, the mixture of BaP and DDT mainly caused some disturbance in osmotic regulation and energy metabolism by differentially altering branched chain amino acids, glutamate, alanine, arginine, unknown metabolite (3.53 ppm), glycine, 4-aminobutyrate, dimethylglycine, homarine and ATP. The results suggest that DDT alone may cause most of metabolites changes in the mixture exposed male mussel gonad, and the results also show that the male P. viridis gonad was more sensitive to DDT than BaP exposures. Proteomic study showed that BaP, DDT and their mixture may have different modes of action. Proteomic responses revealed that BaP induced signal transduction, oxidative stress, spermatogenesis, etc. in the male green mussel gonad; whereas DDT exposure altered proteins that were associated with signal transduction, oxidative stress, cytoskeleton and cell structure, cellular organization, energy metabolism, etc. However, the mixture of BaP and DDT affected proteins related to cytoskeleton and cell structure, oxidative stress, cellular organization, etc. This research demonstrated that metabolomic and proteomic approaches could better elucidate the underlying mechanism of environmental pollutants gonad toxicity.